Study of obstetric and fetal outcome of twin pregnancy in a tertiary care centre - Nandmer, Gurpreet Kaur; Kanhere, Anjali Vivek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The past two decades have witnessed a sharp rise in the incidence of twin and higher order gestations. The progress and developments in assisted reproductive technology, availability and widespread use of ovulation inducing drugs and delayed childbearing are thought to be the causes responsible for the rise. Twin pregnancy is associated with increased maternal and perinatal morbidity and mortality as well as healthcare costs. Maternal complications like hypertensive disorders, anemia, gestational diabetes mellitus (GDM), preterm labour, preterm premature rupture of membranes (PPROM) and placental abruption increases. It is also responsible for repeated antenatal admissions, longer hospital stay, blood transfusions and increase in operative vaginal or cesarean delivery, post-partum hemorrhage and Hysterectomy. Twins have an increased risk of intraventricular hemorrhage, sepsis, necrotizing enterocolitis, respiratory distress syndrome and neonatal death. The objective of the study was to study the maternal and fetal outcome of twin pregnancy. Methods: Retrospective analytical review of all twin deliveries at the teaching hospital medical college of Central India, over a period of 3 years between January 2010 and December 2012.There were 55 twin deliveries, data analysis regarding maternal age, parity, presentation, gestational age at delivery, obstetric complication mode of delivery, birth weights, and perinatal morbidity & mortality was analyzed. Results: Majority of patients 44 (80%) were in age group of 20-30 years. 55% patients were booked and 62% were from urban area. 18 (32%) patients could reach beyond 37 weeks, there were 21 (38%) cases between 34 to 37 weeks and 16 (29%) between 30 to 34 weeks of gestation. Preterm delivery was the commonest complication occurring in 67% of the cases. Cephalic presentation of both the babies occurred in 36% of the cases. 50% of the twins needed admission to NICU for various indications like prematurity, birth asphyxia, low birth weight, meconium staining of liquor & delivery by caesarean section. In our study among the 55 twin births there were 16 (29 %) perinatal deaths and one maternal mortality. Conclusions: Twin pregnancies are high risk pregnancies with more maternal and fetal complications. The use of antenatal care services, identification and anticipation of complications, intrapartum management and good NICU facilities will help to improve maternal and neonatal outcome in twin pregnancies.